Online collaborative dictionary: effects of sense on significant marriage. - Beatriz Curti-Contessoto; Fernanda Correa Silveira Galli (Travessias, 2018)
From the legal point of view, the conception of marriage was modified over time due to changes in Brazilian legislation. However, due to the great complexity involved in this issue, we question whether, in fact, the way the law conceives marriages is in accordance with what Brazilians understand about this institution “outside” the domain of Law specially related to the genre(s) of the spouses and the roles assigned to them in the organization of the conjugal society. In this sense, we present a study carried out in the light of the theory of Discourse Analysis of Pêcheux. Its objective is to interpret the effects of meaning that emerge from some definitions of the significant marriage found in the inFormal Dictionary (2018). This choice was made because it is an online collaborative dictionary that is fed, in large part, by its own users. Thus, based on the notion of discursive formation (DF) and the relation between discourse and memory, we intend to discuss the ideology(ies) that cross these materialities and the subject positions that emerge in the definitions of the significant marriage. In proposing a study such as this, we still hope to problematize the imaginary that emerges in the dictionaries, since in their definitions the “real” and “correct” meanings of words can be found as if they were “free” from a point ideological view of any nature.